Sosialisasi Fungsi Vitamin dan Penggunaan Cairan Antiseptik Berbasis Alkohol dalam Pencegahan Covid 19 di Panti Asuhan Yatim Piatu Ar-Rodiyah Tembalang Semarang - Ana Hidayati Mukaromah; Sarifa H. J. Daud; M. Taroma Arloy; Erick Erianto Arif; Fandhi Adi Wardoyo (Universitas Muhammadiyah Semarang, 2021)
The Covid-19 pandemic (Corona virus) is a pandemic transmitted by the corona virus that attacks humans, especially children and the elderly. The transmission of Covid-19 can be through droplets; therefore, it is necessary to prevent it through health protocol, namely clean and healthy living habits, including using masks, washing hands, maintaining distance, and increase body immunity, The purpose of community service is to provide education about the function of vitamins, and how to use an alcoholic-based antiseptic solution for children Ar-Rodiyah Tembalang Orphanage, Semarang. This activity was carried out by lecturers, D4 Health Analyst students and S2 Clinical Laboratory Science students at Universitas Muhammadiyah Semarang on January 31, 2021. The target of this activity was 51 children aged 8-20 years. The results of the implementation of community service at the Ar-Rodiyah orphanage Semarang were distributing 2 posters about the function of vitamins, and how to use an alcoholic-based antiseptic solution, then during the meeting an explanation of the material and the function of vitamins, and how to use an alcoholic-based antiseptic solution and questions and answers was delivered during the meeting. The conclusion from this community service increase knowledge of orphans about function of vitamin from 30 to 80 and knowledge to use alcohol-based antiseptic fluids correctly can increase from 45 to 90. The orphaned children also really hoped for sustainability of this community service activity with other counseling material.